Circadian clocks are seeing the systems biology light - Hayes, Kevin R (BioMed Central, 2005)
Circadian rhythms are those biological rhythms that have a periodicity of around 24 hours. Recently, the generation of a circadian transcriptional network - compiled from RNA-expression and promoter-element analysis and phase information - has led to a better understanding of the gene-expression patterns that regulate the precise 24-hour clock.